(3TQM NGJeI GdSde HGdETGQIs - (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s
(3ChdgG (B:s
(3NGJeI NW GdHQgGf MjK hLOG ai eGOI s
(3BNQgG (B:s
(3Gddge fhQ bdhHfG ceG fhQJ Hg bdhH hGNJe dfG HGdSYGOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331s
Keywords: (3GdadSaI hGdefWbs